2019
DOI: 10.24831/jai.v47i2.25653
|View full text |Cite
|
Sign up to set email alerts
|

Keragaman Kualitas Buah pada Dua Varietas Okra (Abelmoschus esculentus L. Moench) dari Umur Panen Berbeda

Abstract: Okra (Abelmoschus esculentus L. Moench) is a functional vegetables that has high economic value and it is usedas health purposes due to high bioactive compounds and dietary fiber contents. Okra pod is gradually harvested followsflowering time. The purpose of this study was to evaluate the effect of harvest age on Nitrogen (N), Phosphorus (P), Potassium(K), pigment and phenolic contents of two okra varities. The experiment was conducted from October 2017 to February 2018at IPB experimental station in Leuwikopo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Various kinds of component is suspected to be the cause of the reduced effectiveness as an antibacterial. 19 In contrast to 2.5% NaOCl which only consists of a few chemical elements such as sodium, oxide, and chlorine has a complex antibacterial mechanism through saponification, neutralization and chloramination reactions so that is more effective at inhibiting bacterial growth. 20 Based on the research, it can be concluded that 6.25% and 12.5% green okra extract has inhibition against E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…Various kinds of component is suspected to be the cause of the reduced effectiveness as an antibacterial. 19 In contrast to 2.5% NaOCl which only consists of a few chemical elements such as sodium, oxide, and chlorine has a complex antibacterial mechanism through saponification, neutralization and chloramination reactions so that is more effective at inhibiting bacterial growth. 20 Based on the research, it can be concluded that 6.25% and 12.5% green okra extract has inhibition against E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…The second and third doses of additional fertilizer were applied with blending the manure and 20 L of water, then pour them around the plant base. The harvesting of okra was undertaken at approximately 9 weeks after transplanting (WAP), with the actual harvesting process occurring 6 days after anthesis (DAA), as detailed in Aplugi et al (2019). Time of anthesis was used to determine the optimal harvest age.…”
Section: Methodsmentioning
confidence: 99%
“…According to Aplugi (2019), on average, okra typically start flowering around 36-38 days after transplanting, with 50% flowering occurring at 7 weeks after planting (WAP) and peak flowering at 8 WAP.…”
Section: Leaf Nutrient Contentmentioning
confidence: 99%
“…21 Ekstrak kasar BOH yang menggunakan pelarut organik (etanol) dalam proses ekstraksi seringkali mengandung senyawa yang tidak diinginkan seperti zat warna (klorofil a dan b, karotenoid, antosianin), karbohidrat, lilin, resin. 22 Keberadaan semua senyawa tersebut menyebabkan ketidakstabilan sifat fisika ekstrak ketika akan diformulasikan serta dapat mengurangi kadar senyawa aktif dalam ekstrak. Berbagai macam kandungan tersebut diduga dapat menjadi penyebab berkurangnya efektifitas ekstrak BOH sebagai antibakteri.…”
Section: Pembahasanunclassified